KARAKTERISTIK SUNGAI DI SEKITAR WILAYAH RAWAN LONGSOR DAS CITANDUY - -, Zufialdi Zakaria; -, Irvan Sophian; -, Febri Hirnawan (Fakultas Teknik Geologi Universitas Padjadjaran, 2011)
Characteristics of the river basin in Citanduy landslide prone areas are showing behaviors that can be read via relationship of Suspended Load with discharge. Six rivers studied show different conditions in accordance with the conditions of landslide prone areas around it, also with the condition of each rock. Avalanche region is restricted to several zones of slope stability.Turbidity of the river with small to large are, respectively are S. Cilongkeang, S. Cibarengkok, S. Cilemahurug, S. Cikawung, S. Cinyirib, and S. Cidawolong.River with Sub-watershed wich the most eroded until the lightest on the upstream and the surrounding, respectively are S. Cilongkeang, S. Cilemahurug, S. Cibarengkok, S. Cikawung, S. Cidawolong, and S. Cinyirib.Based on statistical analysis with T-test, S. Cidawolong and S. Cinyirib were not significantly different. In exponential graphics, S. Cilongkeang & S. Cilemahurug, and S. Cibarengkok & S.Cikawung, visually show the same character, but on a statistical analysis with T-test are concluded that significantly different with  = 5%.